Application of Sumudu Decomposition Method to Solve Nonlinear System of Partial Differential Equations - Hassan Eltayeb; Adem Kılıçman (Abstract and Applied Analysis)
We develop a method to obtain approximate solutions of nonlinear system of partial differential equations with the help of Sumudu decomposition method (SDM). The technique is based on the application of Sumudu transform to nonlinear coupled partial differential equations. The nonlinear term can easily be handled with the help of Adomian polynomials. We illustrate this technique with the help of three examples, and results of the present technique have close agreement with approximate solutions obtained with the help of Adomian decomposition method (ADM).